Academic and editorial production of Peruvian public universities. Case: National University of Central Peru - Yangali-Vargas, Jorge (2021)
The National University of Central Peru was founded in 1959. Since then, its academic and editorial production has been maintained until today. Our goal is to chronologically analyze the production of books and journals in this university. It is an exploratory analysis that covers the period 1963-2019. The results show an evolutionary and progressive bibliographic and hemerographic increase. The editorial administration of the teaching and research center, in the current secrecy, gives clear evidence to assume criteria such as open access and internationalization. However, it is concluded that the virtualization of production is urgently needed, which is part of institutional and regional memory.